Clinical case of pregnancy toxaemia in a goat - a case report on veterinary medicine approach - Abdullah, Faez Firdaus Jesse; Lim, Eric Teik Chung; Wan Zakaria, Wan Nurhakimah; Abba, Yusuf; Sadiq, Muhammad Abubakar; Mohammed, Konto; Tijjani, Abdulnasir; Adamu, Lawan; Hambali, Idris Umar; Bitrus, Asinamai Athliamai; Mohd Lila, Mohd Azmi; Haron, Abdul Wahid; et al. (Pashupati Foundation India, 2016)
A pregnant Jamnapari doe was presented with primary complaint of inappetance and recumbency for a week. The most prominent abnormality during physical examination was weakness in both hind limbs typified by difficulty in standing. Ultrasonography revealed that the doe were carrying three viable foetuses that were about 4-months old. Hemato-biochemistry findings showed hypocalcaemia (1.98mmol/L) and hypoglycaemia (2.2mmol/L). Besides that, ketone bodies were also detected from the urine (3+ or 8mmol/L). The doe was treated vigorously for pregnancy toxaemia with 1L of Glucose 20% (G-20) and 5L of 0.9% NaCl, administered intravenously BID for 3 days as glucose replacement and rehydration respectively. 30mL of propylene glycol was also given orally BID for 7 days as glucose precursor. Flunixin meglumine 2.2mg/kg was administered intramuscularly SID for 3 days as non-steroidal anti-inflammatory. In addition, 20mL of theracalcium was given intramuscularly SID for two days and 5mL of Catosal® was given intramuscularly SID for 6 days for calcium supplement and to stimulate body metabolism respectively. One vial (2ml) of methylcobalt was administered intramuscularly SID for 3 days as a nerve supplement and physiotherapy was performed after caesarean section for 10 minutes TID for 6 days in order to increase blood circulation and prevent muscle atrophy. However, the does’ condition started to deteriorate on Day 7 and caesarean was performed on the same day where three foetuses were saved. The doe’s condition improved tremendously and was discharged after a week of caesarean section. This clinical case reports the clinical management of pregnancy toxaemia in a goat, which is a common problem in small holder farms in Malaysia.